2016
DOI: 10.3732/ajb.1600208
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in two pollen self‐incompatibility factors in geographically marginal populations of Solanum habrochaites impact mating system transitions and reproductive isolation

Abstract: Loss-of-function mutations in CUL1 and SLF-23 likely became fixed relatively late during SI to SC transitions, after loss of pistil SI function. Mutations in CUL1 establish unilateral incompatibility with SI populations and strengthen reproductive isolation. Point mutations common to northern and southern SC biotypes likely derive from shared ancestral variants found in more central SI populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(49 citation statements)
references
References 81 publications
4
45
0
Order By: Relevance
“…) and Solanum habrochaites (Markova et al. ) populations. In the selfer A. thaliana , three different causal segregating SC mutations have been identified, possibly associated with distinct ancient glacial refugia (Shimizu et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…) and Solanum habrochaites (Markova et al. ) populations. In the selfer A. thaliana , three different causal segregating SC mutations have been identified, possibly associated with distinct ancient glacial refugia (Shimizu et al.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence suggest that the breakdown of SI has occurred in spatially structured populations in several plant species. For instance, North American populations of A. lyrata show multiple independent breakdowns of SI (Foxe et al 2010) and distinct SC mutations have been found across Leavenworthia alabamica and Solanum habrochaites (Markova et al 2016) populations. In the selfer A. thaliana, three different causal segregating SC mutations have been identified, possibly associated with distinct ancient glacial refugia (Shimizu et al 2008;Durvasula et al 2017;Tsuchimatsu et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Of course, for self‐compatibility to spread throughout a species’ range, it must first become established locally, for example, in marginal populations (Busch ; Griffin and Willi ; Markova et al. ), potentially accompanied by the local purging of inbreeding depression (Busch ; Pujol et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Stone et al (2014) found complete seed discounting in their study of selfcompatibility versus self-incompatibility in W. solanacea, as well as evidence for strong inbreeding depression in SC plants. Of course, for self-compatibility to spread throughout a species' range, it must first become established locally, for example, in marginal populations (Busch 2005b;Griffin and Willi 2014;Markova et al 2016), potentially accompanied by the local purging of inbreeding depression (Busch 2005a;Pujol et al 2009). With the purging of inbreeding depression in part of a species' range, self-compatibility may then spread more easily if at least some of the purged loci are linked to the locus conferring selfcompatibility, thus giving those alleles an additional advantage over those still carrying load in populations that are still SI (Uyenoyama 1997(Uyenoyama , 2004.…”
Section: Reproductive Assurance In Sc Plantsmentioning
confidence: 99%
“…Despite the loss of S-RNase , however, most SC populations of these wild species still exhibit UI against interspecific pollen, indicating UI can also have S-RNase-independent mechanisms. Nonetheless, the degree to which natural intraspecific variation in genes involved in SI might simultaneously affect interspecific isolation via UI remains to be directly investigated in most cases (but see Broz et al 2017, Markova et al 2016).…”
Section: Introductionmentioning
confidence: 99%